Mechanistic Insight into Porous Electrode Impedance: An Example of Ni+YSZ Cermet Anodes. (10th July 2019) - Nenning, Andreas; Gerstl, Matthias; Bram, Martin; Opitz, Alexander Karl
Abstract : Optimization of SOFC electrodes requires detailed insight into their electrochemical processes and rate limiting steps. The impedance spectroscopic investigation of symmetrical cells with two equal electrodes on a solid electrolyte measures not only the area-specific polarization resistance of the electrodes, but physically motivated equivalent circuit modelling and fitting also gives detailed insight into the electrochemical reaction mechanisms and rate limiting processes. In this paper, we give a comprehensive introduction into impedance modeling of porous electrodes and show that a transmission-line type equivalent circuit that is mathematically analogous to the Adler-Lane-Steele model is perfectly applicable to Ni+YSZ cermet anodes. The equivalent circuit fit yields the effective ionic conductivity of the cermet structure, which enables determination of the YSZ phase tortuosity factor. In addition, we can measure the characteristic electrochemically active thickness of the anodes, which gives a direct guideline for the optimal thickness of the fine grained anode active layer in a full SOFC.